Central pontine myelinolysis secondary to hyperglycaemia. Issue 6 (12th July 2016) - Donnelly, Harry; Connor, Steve; Quirk, Jennifer
Abstract : Central pontine myelinolysis is characterised by focal osmotic demyelination within the pons. Its clinical presentation varies, but may include acute paralysis, dysarthria and dysphagia. The cause is traditionally associated with overzealous correction of hyponatraemia in patients who are malnourished, alcoholic or chronically ill. However, it may develop in the context of normal serum sodium, since rapid gradient shifts in brainstem osmolalities can occur in other ways. We present an unusual example of central pontine myelinolysis caused by osmotic shifts secondary to hyperglycaemia in a person with type 1 diabetes mellitus and with consistently normal serum sodium concentrations.